Effects of Exercise Duration and Number of Players in Heart Rate Responses and Technical Skills During Futsal Small-sided Games - Duarte, Ricardo (2010)
In the design of training programs, it is common for coaches to modify task constraints to conduct the drill intensity at the targeted level. Sport specific drills with variations are constantly used in Futsal practices, however the knowledge about how these variations influence drill intensity and technical demands is very scarce. The purpose of this study was to measure the physiological and technical effects of both duration and variations in the numbers of players in futsal specific drills. Heart rates and technical skills of 8 semi-professional futsal players were recorded during four specific drills. The experimental protocol consisted in a half-court game with official rules, played in 4v4, 3v3 and 2v2, each during 4 minutes and 4v4 during 10 minutes. It was maintained an active break of 4 minutes between each repetition. The lowest %HRmax was observed in response to the 4v4 drill independent of the exercise duration. In players’ number variation statistically significant differences were found in the percentage of time spent between 65-85%HRmax, in the number of successive contacts with the ball and number of dribbles. In exercise duration, statistically significant differences were found in percentage of time spent above 85%HRmax, in the number of successive contacts with the ball, number of dribbles and number of tackles. The decrease in the number of players and exercise duration resulted in intensity increases and more frequent individual tactical actions.